It's a fair day, Amber Brown - Danziger, Paula, 1944-; Ross, Tony (New York : G.P. Putnam's Sons, 2002)
Upset with her parents for arguing on what she hoped would be a perfect day, Amber gets lost at a county fair when she tries to follow her best friend Justin and his family through the crowd.
230
Keywords: Lost children -- Fiction; Fairs -- Fiction; Parent and child -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Only child -- Fiction